Pengaruh Persepsi CSR terhadap Reputasi Perusahaan, Minat Beli, dan Kepuasan Pelanggan - Anjelina, Anjelina; Tambunan, Shinta Cristin Natalia (Jurnal Akuntansi Terapan dan Bisnis, 2024)
This research aims to examine the effect of CSR perceptions on customer satisfaction, company reputation and purchase intentions, the influence of customer satisfaction on company reputation and purchase intentions, the influence of customer satisfaction in mediating the relationship between CSR perceptions and company reputation, and the influence of customer satisfaction in mediating the relationship between CSR perceptions and purchase intention. The sample from this research consisted of 200 consumers of Alfamart and Indomaret retail stores in Batam City. Data was collected by distributing questionnaires. The data analysis technique used is multiple regression analysis and Sobel test to test the influence of intervening variables. The research results show that CSR perceptions positively influence customer satisfaction, company reputation and purchase intentions. Customer satisfaction positively influences company reputation as well as purchase intentions. Customer satisfaction indirectly influences the relationship between CSR perceptions of company reputation and purchase intentions. Suggestions for further is research will be able to provide a wider range of respondents by covering fields other than retail to obtain more general information